Eficácia das palmilhas customizadas na distribuição da pressão plantar no pé diabético: ensaio clínico randomizado e controlado. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The aim of this study was to evaluate the influence of customized insoles on plantar pressure in patients with diabetic neuropathy compared to the sham group at the time of the evaluation and after 3 and 6 months. Thus, a randomized, controlled, prospective, triple-blind clinical trial was conducted, with a sample of 46 volunteers who were randomly randomized in a 1: 1 ratio to be directed to the intervention and control groups. This research was conducted according to the standards established for randomized clinical trials (CONSORT). The primary outcome was the analysis of plantar pressure points on the feet of patients with diabetic neuropathy through podobarography in patients in the intervention and control groups. The secondary outcome was the functionality of the foot in activities of daily living through the FAAM questionnaire (Foot and Ankle Ability Measure) in a 6-month follow-up and the analysis of static balance through stabilometry. Despite an apparent intra-group improvement in the 3rd month, there was no significant difference between the groups in the primary and secondary outcomes both in the 3rd and 6th. Thus, it is concluded that the insoles cannot yet be said to provide a significant improvement in the intervention group over the control group in the distribution of plantar pressure in patients with diabetic neuropathy. There is a need for further studies with larger samples and specific adjustments in order to have a more precise level of recommendation.
Effectiveness of customized insoles in the distribution of plantar pressure in the diabetic foot: randomized and controlled clinical trial.
Keywords: Neuropatias diabéticas; Órteses dinâmicas; Calosidade plantar; Diabetic neuropathies; Dynamic orthoses; Callus plantar; CNPQ::CIENCIAS DA SAUDE